Phytochemical Investigation and Antioxidant Effects of Different Solvent Extracts of Pterocephalus Nestorianus Nab. Growing in Kurdistan Region-Iraq - Abdullah, Fuad O.; Hussain, Faiq H.S.; Cucca, Lucia I.; Vidari, Giovanni (Science Journal of University of Zakho, 2018)
The medicinal plants have been used as a herbal tradition in Kurdistan. Most of the medicinal plants are still not investigated from a phytochemical and biological activity. Therefore, different solvent extraction carried out to study phytochemicals and antioxidant activity of Pterocephalus nestorianus Nab. Through this research, it is reported for the first time that the phytochemicals and antioxidant activity on P. nestorianus Nab. collected at Safeen Mountain in Erbil-Iraq, which was known as a Lawa in Kurdistan. It is used against inflammation and oral diseases. The phytochemical study of four extracts (Hexane, ethyl acetate, methanol and methanol 70%) of P. nestorianus flowers, leaves and roots revealed that it contains rich phytochemical composition. C4H8O2 and CH3OH extracts of P. nestorianus showed a high radical scavenging activity compared with trihydroxy benzoic acid as a standard. The flavonoid and phenolic presence showed strong correlation with the antioxidant activity.